P-752 Fertility outcomes after hysteroscopic niche resection compared with expectant management in patients with a niche in the uterine cesarean scar. (30th June 2022) - He, C; Yan, L; Zhu, C; Zhang, J; Mol, B.W; Huirne, J.A
Abstract: Study question: Whether hysteroscopic niche resection is suitable for patients with a niche in the uterine cesarean scar and with fertility desire compared with expectant management. Summary answer: Hysteroscopic niche resection is a effective treatment for patients with fertility desire compared with expectant management and satisfactory obstetrical outcomes could be achieved. What is known already: The specific treatment method for niche should be determined according to the patient's symptoms, fertility desire and niche features, up to now, hysteroscopic niche resection has been shown effective to reduce abnormal uterine bleeding. However, similar to expectant treatment, hysteroscopic niche resection does not reconstruct the lower uterine segment, whether hysteroscopic niche resection affect fertility outcomes remains controversial. Study design, size, duration: We designed a single-center retrospective cohort study. We included patients with desire to conceive that underwent hysteroscopic niche resection or expectant management between 2016.9-2020.12. The date of entry for each woman was the date of treatment or the date that the niche was diagnosed. The last day of analysis was the date of the first delivery or the last follow-up visit in women who remained non-livebirth. Participants/materials, setting, methods: This study was conducted in a university-affiliated gynecology hospital. A total of 71 patients that underwent hysteroscopic niche resection and 97 patients that underwent expectant management were recruited. All women were followed up yearly until December 2021 for the occurrence of live birth. A Cox proportional hazards regression model with potential variables to identify predictors of pregnancy was also processed. Main results and the role of chance: Baseline characteristics of age, gravidity, parity, previous cesarean section, and anatomical indicators of niche were not significantly different between the groups. However patients in the hysteroscopic niche resection had a longer menstruation duration (hysteroscopic niche resection vs expectant management as 12(10/14) vs 7(7/10), P <0.001 ) and a longer infertility period before treatment(hysteroscopic niche resection vs expectant management as 48.00±36.28 vs 23.11±20.34, P = 0.014 ). The overall live birth rate was similar in both groups (hysteroscopic niche resection vs expectant management as 37/71 [52.11%] vs 40/97 [41.23%], P = 0.162 ). For the live births in the two groups, no uterine rupture occurred.The total pregnancy rate was higher in the hysteroscopic niche resection group (hysteroscopic niche resection vs expectant management as 50/71 [70.40%] vs 50/97 [51.54%], P = 0.014 ). What's more, for patients with infertility before treatment, there was a statistically significant difference regarding time to pregnancy between the two groups ( P = 0.049 ). After adjustment for confounding factors including age, numbers of cesarean section, infertility peroid before treatment, anatomical indicators of niche and menstruation duration, cox proportional hazards analysis revealed that women underwent hysteroscopic niche resection were positively correlated to pregnancy (AHR = 1.646, 95% CI [1.081-2.506]). Limitations, reasons for caution: This study was a single-center retrospective cohort study, to strengthen the conclusion, more prospective studies that include larger sample sizes and multiple centers should be conducted. Wider implications of the findings: For asymptomatic cesarean scar defect patients whose residual myometrium thickness is sufficient, the expectant treatment is practical. However, for patients with abnormal uterine bleeding or infertility, hysteroscopic niche resection should be recommended. Trial registration number: not applicable